Bilateral Leg Compartment Syndrome After Prolonged Lithotomy Position. Clinical Case Report - Díez-Albero, Luis; Moril-Peñalver, Lorena; Lapeña-Martínez, Andrés; López-Prats, Fernando (Revista Chilena de Ortopedia y Traumatología, 2021)
Background Compartment syndrome is a rare but severe complication resulting from a prolonged lithotomy position and the use of leg loops.Purpose To present a case of bilateral compartment syndrome after prolonged lithotomy position associated with the use of leg loops.Methods A 43-year-old man underwent urological surgery in the usual lithotomy position for a 6-hour period. Two hours after the end of the surgery, the patient presented severe pain and stiffening of the anterior and lateral compartments of both legs, elevated serum creatine kinase levels (the baseline value of 109 U/L increased to 7,689 U/L at 12 hours), and inability for passive dorsiflexion of both ankles. The patient reported no pain in the other compartments.Results Suspicion of an anterolateral compartment syndrome resulted in an urgent bilateral fasciotomy; muscle perfusion was decreased, and it improved after fascial opening. Dressings were changed every 48 hours, and tissue viability was observed until the final closure at 4 days. At two weeks, the patient presented slight fatigue when walking with no assistance, in addition to swelling in the lateral compartment of both legs. Ten months after surgery, the patient walked with no assistance and with complete muscle function.Conclusion Knowledge of the association between compartment syndrome and prolonged laparoscopic surgery is essential for an early diagnosis and immediate surgical treatment to avoid serious sequelae. In our patient, the good outcomes resulted from quick action, since diagnosis is often delayed. Limiting the lithotomy position to those surgical moments in which it is essential and changing the position of the legs every 2 hours during prolonged procedures can reduce the occurrence and incidence of compartment syndrome, preventing this complication.
Keywords: compartment syndrome; lithotomy; leg loops; fasciotomy; intracompartmental pressure